Expo 2016 Antalya final report : a green life for future generations - ? ([Ankara]: [Presidency of the Republic Of Turkey], 2017)
TABLE OF CONTENTS
Executive Summary General İnformation Organizational Structure Participant
Keywords: Expo (International Exhibitions Bureau) (2016 : Antalya, Turkey)